Birefringence and dispersion of cylindrically polarized modes in nanobore photonic crystal fiber - Euser, T. G.; Schmidt, M. A.; Joly, N. Y.; Gabriel, C.; Marquardt, Christoph; Zang, L. Y.; Foertsch, M.; Banzer, Peter; Brenn, A.; Elser, Dominique; Scharrer, Michael G; Leuchs, Gerd; et al. (Journal of the Optical Society of America B-Optical Physics, 2011)
We demonstrate experimentally and theoretically that a nanoscale hollow channel placed centrally in the solidglass core of a photonic crystal fiber strongly enhances the cylindrical birefringence (the modal index difference between radially and azimuthally polarized modes). Furthermore, it causes a large split in group velocity and group velocity dispersion. We show analytically that all three parameters can be varied over a wide range by tuning the diameters of the nanobore and the core.© 2010 Optical Society of America.
CRIS-Team Scopus Importer:2022-06-05